Current challenges facing the assessment of the allergenic capacity of food allergens in animal models. Issue 1 (December 2016) - Bøgh, Katrine; Bilsen, Jolanda; Głogowski, Robert; López-Expósito, Iván; Bouchaud, Grégory; Blanchard, Carine; Bodinier, Marie; Smit, Joost; Pieters, Raymond; Bastiaan-Net, Shanna; Wit, Nicole; Untersmayr, Eva; et al.
Abstract Food allergy is a major health problem of increasing concern. The insufficiency of protein sources for human nutrition in a world with a growing population is also a significant problem. The introduction of new protein sources into the diet, such as newly developed innovative foods or foods produced using new technologies and production processes, insects, algae, duckweed, or agricultural products from third countries, creates the opportunity for development of new food allergies, and this in turn has driven the need to develop test methods capable of characterizing the allergenic potential of novel food proteins. There is no doubt that robust and reliable animal models for the identification and characterization of food allergens would be valuable tools for safety assessment. However, although various animal models have been proposed for this purpose, to date, none have been formally validated as predictive and none are currently suitable to test the allergenic potential of new foods. Here, the design of various animal models are reviewed, including among others considerations of species and strain, diet, route of administration, dose and formulation of the test protein, relevant controls and endpoints measured.